ONLINE CLASS EXPERIENCES OF NEPALI STUDENTS AND TEACHERS - Kumar Kshetree, Arun (Department of Biology Education, Faculty of Teacher Training and Education, Universitas Wijaya Kusuma Surabaya, 2024)
This research paper presents a case study analysis of the experiences of master's degree students during online classes amidst the COVID-19 pandemic, focusing on participants from Butwal, Nepal and various other regions. The study involved interviews with ten students and five teachers who actively engaged in online learning during this period. The findings reveal that the COVID-19 pandemic had a profound impact, leading to widespread disruptions, including significant economic challenges that continue to affect many nations. The pandemic altered nearly every aspect of human life, bringing about substantial changes in people's lifestyles. The study highlights that a majority of students encountered difficulties related to internet connectivity, which hindered their ability to participate in classes effectively and grasp key concepts. Moreover, many students reported lack of adequate knowledge of online learning tools, further complicating their educational experience. Similarly, teachers reported facing challenges in managing online classes, primarily due to issues with internet connectivity. The insights gained from this study underscore the need for enhancing teachers' technical proficiency and call for improved regulation of internet and electricity services to better support online education in future crises.